2017
DOI: 10.1111/ejh.12870
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle delivery systems, general approaches, and their implementation in multiple myeloma

Abstract: Multiple myeloma (MM) is a hematological malignancy that remains incurable, with relapse rates greater than 90%. The main limiting factor for the effective use of chemotherapies in MM is the serious side effects caused by these drugs. The emphasis in cancer treatment has shifted from cytotoxic, non-specific chemotherapies to molecularly targeted and rationally designed therapies showing greater efficacy and fewer side effects. Traditional chemotherapy has shown several disadvantages such as lack of targeting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 122 publications
1
29
0
1
Order By: Relevance
“…One potential approach to improve the efficacy and reduce the toxicity of treatment is to encapsulate the PI in a nanoparticle and add targeting elements which will increase the specific accumulation of the particle (and the PI within) to the tumor 13,19 . We previously demonstrated that BTZ loaded into a chitosan nanoparticle and decorated with anti-CD38 antibodies improved the accumulation of BTZ in MM cells, which overexpress CD38, and reduced the toxicity of BTZ in normal tissue 14 .…”
Section: Discussionmentioning
confidence: 99%
“…One potential approach to improve the efficacy and reduce the toxicity of treatment is to encapsulate the PI in a nanoparticle and add targeting elements which will increase the specific accumulation of the particle (and the PI within) to the tumor 13,19 . We previously demonstrated that BTZ loaded into a chitosan nanoparticle and decorated with anti-CD38 antibodies improved the accumulation of BTZ in MM cells, which overexpress CD38, and reduced the toxicity of BTZ in normal tissue 14 .…”
Section: Discussionmentioning
confidence: 99%
“…NPs drug delivery systems allow the delivery of larger doses of chemotherapies and increase the drug bioavailability into targeted areas, thus sparing healthy tissues [13]. Chitosan has been widely used in drug delivery systems.…”
Section: Discussionmentioning
confidence: 99%
“…However, this liposomal formulation showed reduced cytotoxic effects in MM cells compared to free BTZ, attributed to the kinetics of BTZ release from their NPs. Moreover, these particles were relying on passive targeting to the tumor through enhanced permeability and retention (EPR) effect, which is the tendency for NPs and other molecular agents to conglomerate more in tumor versus normal tissue [13-15]. But in addition to the unspecific nature of the EPR effect, large tumors may not display the EPR effect, thus causing for fewer NPs to accumulate in the central areas [16].…”
Section: Introductionmentioning
confidence: 99%
“…Nanomedicine approaches offer the potential of enhanced and more personalized therapeutics in MM with a reduced risk of off-target effects (Table 1). Current treatments in MM rely on immunomodulatory drugs such as lenalidomide combined with proteasome inhibitors (PI) such as bortezomib (De La Puente and Azab, 2017). The introduction of PI inhibitors has contributed to major improvements in patient survival, but off-target effects, in particular neurotoxicity, remain a major concern (Richardson et al, 2009).…”
Section: Liposome-based Targeted Delivery In MMmentioning
confidence: 99%